Journal of Marine Science: Research & Development - OMICS International (OMICS International, 2026)
Journal of Marine Science: Research & Development is an Open Access Publisher that aims to publish studies on the ocean, its ecosystems and its life forms as well as the coastal environments, oceanic currents and the sea floor.
Keywords: Ciencias del mar; Revistas depredadoras; Predatory journals